2011
DOI: 10.1002/pip.1131
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimprinted Tio2 sol–gel passivating diffraction gratings for solar cell applications

Abstract: We report the fabrication and characterization of TiO2 sol–gel diffraction gratings on silicon substrates by using nanoimprint lithography. The gratings are homogeneous and free of defects and cover an area of 25 cm2. Minority carrier lifetimes of up to 900 µs for imprinted samples under illumination are reported, which Kelvin probe measurements indicate is due to light‐generated negative charge in the films. The structures reported here are very promising as light‐trapping, passivating coatings for solar cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…In general, the surface passivation mechanisms of TiO 2 on c‐Si are still under investigation. Band bending, negative charges density in the TiO x film, presence of SiO 2 ‐like interface layer whether grown intentionally or generated via diffusion of O atoms from TiO x to c‐Si, and hydrogenation all are the most‐likely mechanisms for the surface passivation of c‐Si with TiO x . However, one of the most well‐documented methods to achieve improved surface passivation and high efficiency with TiO x dielectric is the insertion of SiO 2 ‐like interface layer at c‐Si/TiO x boundary .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the surface passivation mechanisms of TiO 2 on c‐Si are still under investigation. Band bending, negative charges density in the TiO x film, presence of SiO 2 ‐like interface layer whether grown intentionally or generated via diffusion of O atoms from TiO x to c‐Si, and hydrogenation all are the most‐likely mechanisms for the surface passivation of c‐Si with TiO x . However, one of the most well‐documented methods to achieve improved surface passivation and high efficiency with TiO x dielectric is the insertion of SiO 2 ‐like interface layer at c‐Si/TiO x boundary .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, electrons can pass through a TiO x layer whereas holes are repelled off from the heterojunction . Previously, it has been reported that TiO x layers can be deposited on c‐Si by several techniques such as chemical vapor deposition and spin coating . Among them, ALD‐TiO x thin layers have been intensely investigated since it functions as a good passivation layer for c‐Si surface due to the low deposition damage to c‐Si surface and the ability to fabricate sub 5 nm thick films.…”
Section: Influence Of the Siox Interlayers Prepared By Different Chemmentioning
confidence: 99%
“…section 3.4), which we estimate from a one-diode model to about Δ , ≈ 3 . Therefore, the increased Voc of silicon thin-film solar cells on SMART superstrates might be attributed to passivation properties of the TiOx layer, which are already known from literature [27][28][29][30]. However, further investigations are needed in order to elucidate this hypothesis, e.g.…”
Section: Materials Qualitymentioning
confidence: 86%